Electron beam irradiation of typical sulfonamide antibiotics in the aquatic environment: Kinetics, removal mechanisms, degradation products and toxicity assessment. (July 2021) - Zhu, Feng; Pan, Jiali; Zou, Qi; Wu, Minghong; Wang, Hongyong; Xu, Gang
Abstract: Due to their widespread use and harmful effects on aquatic environment, sulfonamide antibiotics (SAs) have become an emerging pollutant of great concern around the world. In this study, we investigated the degradation process and mechanism of sulfamerazine (SMR), sulfadiazine (SDZ), and sulfapyridine (SPD) by electron-beam irradiation (EBI). The results showed that the three SAs were well suited to the pseudo-first-order reaction kinetics, and they could be almost completely removed with high efficiency (5 kGy). Among the environmental factors, pH (3.0) and O2 atmosphere can further enhance the removal of the sulfonamides (SAs), while NO2 − has the most pronounced degrading inhibitory effects among the many ions, these results illustrate that hydroxyl radicals play a dominant role. Compared with SMR and SDZ, the degree of mineralization of lower molecular weight SPD is obvious (45%). LC-MS and DFT calculations indicate that the concentrations of degradation products of the three SAs show a tendency to increase and then decrease, demonstrating that EBI can achieve efficient removal and further mineralization of SAs. Meanwhile, the results of the common product 4-Aminophenol produced during the degradation process further indicate that HO is the predominant reactive oxygen species (ROS). In addition, acute toxicity experiments with luminescent bacteria and predictions of ECOSAR procedures proved the toxic effects greatly decreased after the degradation. This study provides new ideas for achieving efficient and profound removal of emerging pollutants from the aquatic environment. Graphical abstract: Image 1 Highlights: Electron beam irradiation can remove SAs efficiently. HO played vital roles in decomposition process. The possible pathway was proposed combining LC-MS and DFT calculation. Quantitative analysis of the degradation products was done. Luminescent bacteria test and the ECOSAR were combined to assess the ecotoxicity.